2015
DOI: 10.5694/mja15.00596
|View full text |Cite
|
Sign up to set email alerts
|

Life expectancy discussions in a multisite sample of Australian medical oncology outpatients

Abstract: Objectives: The study examined: 1) the proportion of patients who received their preferred level of information about life expectancy; and 2) sociodemographic, clinical and psychological factors associated with patients' perceptions of whether they received too little, too much, or the right amount of information about life expectancy. Design: Cross‐sectional survey. Setting: Eleven large Australian medical oncology treatment centres. Participants: A total of 1431 medical oncology outpatients participated (81%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 105 publications
1
6
0
Order By: Relevance
“…This requires that patients have an accurate perception of curability of disease. Consistent with findings from previous studies, [32][33][34] a quarter of the patients surveyed herein reported that they were not getting the information they wanted about their life expectancy. Most patients prefer their doctor to ask them before discussing the impact that cancer might have on their life expectancy.…”
Section: Discussionsupporting
confidence: 90%
“…This requires that patients have an accurate perception of curability of disease. Consistent with findings from previous studies, [32][33][34] a quarter of the patients surveyed herein reported that they were not getting the information they wanted about their life expectancy. Most patients prefer their doctor to ask them before discussing the impact that cancer might have on their life expectancy.…”
Section: Discussionsupporting
confidence: 90%
“…Perceived importance of prognosis disclosure was not examined. However, previous studies in the literature indicate that the majority of patients perceive this to be an important part of their cancer care [3941]. Additionally, restricting the question to willingness to participate in ACP in the next month- rather than a longer timeframe- may have also reduced the number of participants who were willing to engage.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, only two‐thirds (64%) of respondents had discussed life expectancy information with at least one cancer care provider. This may have been a product of patient preference, as previous studies indicate that not all patients want to know their life expectancy (Mackenzie et al, ; Zafar et al, ; Zucca et al, ). There are a number of published frameworks, such as the “Serious Illness Conversation Guide,” that help cancer care providers to determine whether patients want to receive life expectancy information, and to deliver this information in a manner that it can be understood and recalled (Bernacki & Block, ; Gilligan et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Between 50% and 70% of cancer patients want to be told their life expectancy (Mackenzie et al, 2018;Zafar et al, 2016;Zucca et al, 2015). However, variation in approaches to communication about issues such as life expectancy has been reported in different patient groups (Gysels et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation